Toll‐like receptors 3, 7, 8, and 9 in gastric cancer. Issue 2 (25th November 2022) - Eskuri, Maarit; Kemi, Niko; Helminen, Olli; Huhta, Heikki; Kauppila, Joonas H.
Abstract : Toll‐like receptors (TLRs) have been shown to have anti‐tumor, pro‐tumor, or even dual effects in cancer, and are thus potential prognostic biomarkers and immunotherapeutic targets. The present study aimed to evaluate associations between endosomal TLRs, namely TLR3, TLR7, TLR8, and TLR9, expression and clinicopathological variables and survival in gastric cancer. A total of 564 gastric adenocarcinoma patients were included in this retrospective cohort study. Samples and clinicopathological data were retrieved and organized into tissue microarray blocks. Protein expressions were detected by immunohistochemical staining. The patients were divided into low expression and high expression groups by median values of expression. Cox regression provided hazard ratios (HR) with 95% confidence intervals (CI), adjusted for confounders. Patients with high nuclear TLR3 expression had significantly poorer 5‐year survival than the low nuclear TLR3 expression group in the univariable analysis (crude HR 1.31, 95% CI 1.07–1.60). With radically resected patients, poor prognosis was also seen in the multivariable analysis (adjusted HR 1.38, 95% CI 1.08–1.77). Cytoplasmic TLR3, TLR7, TLR8, and TLR9 were not associated with 5‐year survival. In conclusion, high nuclear TLR3 expression seems to have prognostic impact in gastric cancer, while TLR7, TLR8, and TLR9 do not.